2011
DOI: 10.1186/1478-7954-9-6
|View full text |Cite
|
Sign up to set email alerts
|

Regional inequalities in under-5 mortality in Nigeria: a population-based analysis of individual- and community-level determinants

Abstract: BackgroundRegions with geographically diverse ecology and socioeconomic circumstances may have different disease exposures and child health outcomes. This study assessed variations in the risks of death in children under age 5 across regions of Nigeria and determined characteristics at the individual and community levels that explain possible variations among regions.MethodsMultilevel Cox proportional hazards analysis was performed using a nationally representative sample of 6,029 children from 2,735 mothers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
70
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 31 publications
16
70
1
1
Order By: Relevance
“…As previously found (Antai, 2011b), this result indicates region of residence where children were born or raised as important contextual factors influencing under-five mortality in Nigeria. In particular, the results demonstrated that while characteristics of the neighbourhood contexts appear to alleviate under-five mortality risks in the South-west Nigeria, community characteristics tend to aggravate risks of under-five mortality in other regions, especially North-east, North-west and South-south.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As previously found (Antai, 2011b), this result indicates region of residence where children were born or raised as important contextual factors influencing under-five mortality in Nigeria. In particular, the results demonstrated that while characteristics of the neighbourhood contexts appear to alleviate under-five mortality risks in the South-west Nigeria, community characteristics tend to aggravate risks of under-five mortality in other regions, especially North-east, North-west and South-south.…”
Section: Discussionsupporting
confidence: 66%
“…Although, the effect of neighbourhood contexts on child survival has been recognised in a number of countries in sub-Saharan Africa (Antai, 2011b;Boco, 2010;Omariba, et al, 2007) and elsewhere (Sastry, 1997), evidence is sparse on the effects of neighbourhood contexts on under-five mortality in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…This is possibly because those who utilize these services are educated, were provided with information on the benefits of birth registration, and were subsequently linked to the registration centers after delivery. A poor pattern of maternal hospital utilization has been observed to negatively influence the chances of survival of children under five years (Antai 2011). Thus improving hospital utilization for delivery, besides having a direct effect on the health of the women concerned, can contribute toward raising birth registration completeness in Nigeria while also improving outcomes for the children born to these women.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of employment distribution is very common in developing countries, but the problem of disparity in employment among nations and among the different regions of any nation is not only restricted to Nigeria (Akpan, 2000;Antai, 2011). Regional inequality in employment has become more perturbing in Nigeria due to the imbalance in income distribution among geopolitical zones.…”
Section: Introductionmentioning
confidence: 99%